P‐101: Self‐Capacitive Ring Like Touch Sensor Design and Algorithm for OLED On‐Cell Touch Panel. Issue 1 (28th June 2022) - Lin, Yi-Ying; Lai, Chih-Chang; Lin, Ching-Chung
Abstract : In this paper, the self‐capacitive ring like touch sensor design and algorithm for OLED on‐cell touch panel is proposed by rearranging the touch sensor pad, and using hybrid algorithm to calculate touch position. Base on ring like touch sensor design and hybrid algorithm, we can improve the touch accuracy of ring region and realize sliding function on smart watch edge without real rotating bezel mechanical parts.